ASSESSMENT OF CARIES PREVALENCE AND ASSOCIATED RISK FACTORS AMONG TURKISH CHILDREN IN EDIRNE, TURKEY - Sinem Batur Kara; Betul Kargul; Sirin Guner Onur; İlknur Tasdemir (Cumhuriyet University, 2020)
Objectives: Dental caries has a multifactorial etiology that has been associated with many risk factors such as improper dietary habits, poor oral hygiene, parental education and socioeconomic status of family. It is essential to identify the potential risk factors to improve the oral health of children. The aim of the present study is to evaluate dental caries prevalence and potential risk factors in a group of Turkish children residing in Edirne province. Materials and Methods: Data of 704 children aged between 7 to 12 years old, who applied for examination/treatment to the Department of Pediatric Dentistry between April 2016 through June 2018 were evaluated for the present study. Dental caries status was recorded using the number of decayed, missing or filled teeth (dft/DMFT) and decayed, missing or filled surface (dfs/DMFS) indices. A structured questionnaire inquiring sociodemographics information, oral hygiene habits, and diet history of the children were employed to parents. Results: The sample comprised of 365 males and 339 females. From overall children, 31.11 % were caries-free, while the caries prevalence was found 68.89%. Dental caries scores of all children included in the study were calculated as dft:4.97±4.02, dfs:11.85±11.82 for primary teeth and as DMFT:2.63±2.42 DMFS: 3.81±4.34 for permanent teeth. Statistically significant differences were found between age groups according to caries prevalence in the primary dentition (p<0.05). Dental caries was associated with educational level of mother (p<0.05), educational level of father (p=0.02), gender (p= 0.007) and family income (p=0.03). Conclusions: The high prevalence of dental caries highlights the importance of comprehensive oral health interventions to improve the oral health of children residing in Edirne, Turkey.